(untitled) (مجلة إحالات, 2026)
Children’s theater is one of the most important means of education, as it plays a role It is important in instilling educational and moral values in the hearts of children. Therefore, this research paper will introduce children’s theater and its most important features, with a focus on the most important educational and moral values contained in “The Skilled Fisherman’s Play.” Through which the writer tried to provide a set of advice and instructions that benefit children in particular, it is also loaded with a set of educational values that contribute to raising the child in a sound upbringing. In this play, an easy language was adopted that suits this age group.